An organizational economics approach on the pursuit of socioemotional and financial wealth in family firms: Are these competing or complementary objectives?. (21st November 2016) - Kabbach de Castro, Luiz Ricardo; Crespi-Cladera, Rafel; Aguilera, Ruth V.
Abstract : Purpose: The purpose of this study is to analyze the contribution of the paper by Martin and Gomez-Mejia and propose complementary approaches and ways to test their hypotheses. Design/methodology/approach: This study compares different theoretical approaches that complement socioemotional wealth to explain manager's decisions and firm performance. Findings: The authors of this study argue that progress could be achieved by combining Martin and Gomez-Mejia's propositions with elements of existing organizational theories that are grounded on economics such as the resource-based view, transactional cost and property rights. Originality/value: This study provides a new perspective of the work of Martin and Gomez-Mejia published in this issue.